Relações entre características pessoais, comportamento e desempenho de micro e pequenos empresários do setor industrial de Fortaleza - Silva, Francisco Rogério de Morais (2009)
This study investigates the relations between personal characteristics, trends of character and strategies adopted by entrepreneurs and its relation with the success of small companies of the industrial sector of Fortaleza, whose activities had initiated in 2005, working for at least two years. Among the concepts considered in the work, the peculiarities of the segment of micro and small companies, the origin of the company unit and its main theoretical lines, personality characteristic and character traits, business strategies and the success are highlighted. We used a sample of one hundred entrepreneurs, from which we got a characteristic demographic profile, differentiating it from the business profile of other sectors related to personal, strategic aspects, success and business aspects, strengthening the idea that it is a differentiated group that needs to be approached with a proper methodology and differently understood. Aspects related to human capital (formation, personal experiences, specific qualification and experiences in other business and family situations) are added to other factors analyzed in the formation of this specific professional group. The analysis of the data collected shows that, similarly to what was proven in previous studies, certain personal characteristics are more associated to a good business performance, and such association is strengthened by strategies relevant for this kind of businessperson. Besides proving conclusions of previous studies about these relations, the present work revealed that it is possible to identify character traits that, added to or identified with personal characteristics and psychological or business strategies, improve the business performance. A predominant trend of the following styles of character in the searched group was identified: civic and collectivist individualist followed by heroic, narcissist and obsessive individualist. The awareness of their ability, assuming work as a supreme value, sharing their decisions and the capacity of reassessing from their own mistakes, were some characteristics related to the styles: civic and collectivist individualist. The study evidenced that entrepreneurs with good performance indices are also the most satisfied and fulfilled at the personal and professional levels, strengthening the relationship between objective and subjective success. Among the most employed strategies: “business guidance for the performance of the company and its employees”, “practice of innovation and use of creativity” and “professionalism” are the most effective for attaining business success.